2004
DOI: 10.1183/09031936.04.00141303
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of exercise-induced asthma with beclomethasone dipropionate in children with asthma

Abstract: A new hydrofluoroalkane-beclomethasone dipropionate (HFA-BDP) aerosol markedly increases drug delivery to the airways. Therefore, even low doses of HFA-BDP should be effective, and the present study assesses this.A randomised, double-blind, crossover study was used to compare the effect of placebo, HFA-BDP 50 mg or 100 mg given q.d. (QVAR TM Autohaler TM ; 3M Pharmaceuticals, St. Paul, MN, USA) on exercise-induced bronchoconstriction and exhaled nitric oxide (eNO). After a 14-day run-in, 25 children (5-14 yrs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…Petersen et al 18 revealed that a 4-week treatment with low-dose beclomethasone exerted a significant reduction in airway hyperreactivity to exercise in 25 children with mild intermittent or mild persistent asthma. Their study showed a reduction in maximum fall in FEV 1 after exercise from 28% to 21%, similar after treatment with 2 doses of beclomethasone-50 mg and 100 mg. 18 Similarly, in our study, 4-week treatment with low-dose budesonide decreased the grade of exercise-induced bronchial hyperreactivity, with maximum percentage fall in FEV 1 after exercise reduced from 25% to 17%. The magnitude of the protective effects in all other studies [19][20][21][22] seemed greater than the effects achieved in our study and in the study by Petersen et al 18 Opposite to all remaining studies (twice daily dosing ICS), the study by Petersen et al 18 dosed beclomethasone dipropionate once daily, which can be less effective.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Petersen et al 18 revealed that a 4-week treatment with low-dose beclomethasone exerted a significant reduction in airway hyperreactivity to exercise in 25 children with mild intermittent or mild persistent asthma. Their study showed a reduction in maximum fall in FEV 1 after exercise from 28% to 21%, similar after treatment with 2 doses of beclomethasone-50 mg and 100 mg. 18 Similarly, in our study, 4-week treatment with low-dose budesonide decreased the grade of exercise-induced bronchial hyperreactivity, with maximum percentage fall in FEV 1 after exercise reduced from 25% to 17%. The magnitude of the protective effects in all other studies [19][20][21][22] seemed greater than the effects achieved in our study and in the study by Petersen et al 18 Opposite to all remaining studies (twice daily dosing ICS), the study by Petersen et al 18 dosed beclomethasone dipropionate once daily, which can be less effective.…”
Section: Discussionmentioning
confidence: 58%
“…However, in the current study, ICSs were administered twice daily with protective effects similar to the results of the study by Petersen et al 18 Twelve-week treatment with budesonide 100 or 200 mg/d reduced the postexercise fall in lung function from 25% to 5% to 7%, 21 and 3-week treatment with fluticasone propionate 100 mg from 33% to 9%. 19 Results of many studies with a single dose of LABA revealed their protection effectiveness against EIB in children with asthma.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Jonasson [81] demonstrated that 3 months of low-dose budesonides administered once or twice daily relieved exercise intolerance and symptoms in subjects with mild asthma with EIA. Studies by Peterson et al [96] with HFA beclomethasone and Subbarro et al [97] using the prodrug ciclesonide demonstrated efficacy over 4 weeks in dose response fashion.…”
Section: Pharmacotherapy/nonpharmacotherapy Treatment Of Eibmentioning
confidence: 96%
“…A previous study of 50 mg and 100 mg of hydrofluoroalkane-delivered beclomethasone dipropionate administered once daily showed similar levels of protection (approximately 30%) after 4 weeks of treatment. 16 However, in a study with budesonide at 100 mg/d, the degree of protection was similar whether budesonide was administered once or twice daily. 14 It is unlikely that the mode of delivery accounts for this discrepancy because both this study and the report of Petersen et al 16 used hydrofluoroalkane formulations, which have higher pulmonary drug deposition than the Turbuhaler.…”
Section: Discussionmentioning
confidence: 95%